Constituição do saber-poder da psicologia brasileira e a medicalização da infância em contexto escolar - Arditti, Roberta Gusmão (2023)
This dissertation aims to analyze the relationship between the productions of knowledge-power in Brazilian Psychology and the historical roots of the medicalization of childhood in a school context. To achieve this, a post-structuralist theoretical-methodological approach was adopted, which problematizes the relations of power and knowledge that permeate discourses and social practices. Inspired by Foucauldian genealogy, the research carries out a historical and critical analysis of the pre-institutional phase of Brazilian Psychology, seeking to explain how its knowledge was constituted/configured in Brazilian territory, in interface with the demands of Education and medicine. We sought to highlight the contingencies that enabled the production and emergence of this knowledge, linking it to the webs of power that circulate in the social fabric and that, at the intersection of knowledge and power, give rise to “scientific” discourses that produce subjects, subjectivities, norms and produce massively diagnosed, pathologized children. Medicalization in the school context is linked to the production of “diseases of non-learning”, which constitute a school problem, supposedly resolved by Medicine and Psychology, which tends to summarize the body and the demands of childhood in purely biological questions. In this research, medicalization is situated as a biopower device, a technique for normalizing the population. The research highlights the role of Psychology in the genesis and production of the phenomenon of the medicalization of childhood and maintains that this is not a recent phenomenon, but rather a founding, constituent, of the category of childhood, of the school institution and of psychological knowledge itself.